“Implementación de un aplicativo web para la gestión de procesos de información de la Facultad de Ciencias Administrativas en la Universidad Técnica de Cotopaxi” - Barragán Cuenca, María Fernanda (2021)
This technological proposal was made at the Faculty of Administrative and Economic Sciences of the Technical University of Cotopaxi where inconveniences were evident in the administration of received and issued documentation, therefore its objective was the development of a web application for the Management of content of information, for which the application of methods such as qualitative, quantitative, bibliographic and complemented with field research aspects was carried out, which allowed to better specify the foundation of the state of the art and on the other hand, different tools were used for the development of the web application among them: lucidchart, Bootstrap, PHP, HTML, for a better understanding of the processes the survey and interview were used whose aspects supported to define the user stories, the main element and as management for the project, SCRUM.